COMPARATION OF MEDIATION IN THE COURT AND OUTSIDE THE COURT IN RESOLVING STATE ADMINISTRATIVE CASES - Izza, Nurul; Sulistyo, Ahmad Bayu (International Journal of Kita Kreatif, 2024)
Disputes in legal relations that arise in the community are a natural thing as a result of a consequence of the legal relationship. In practice, the process of resolving disputes can be carried out within the court and outside the court, the determination of which is chosen by the disputing party. In the process before a dispute resolution is carried out, mediation efforts are made first. which aims to take steps that are mutually beneficial to both parties to the dispute. Regarding the mediation effort, it raises the question whether the process ns equally between mediation carried out in court and mediation efforts carried out outsde the court Dispute resolution as mediation has been known since the first in Indonesia because of the customs system in resolving a case always uphold discussion and consensus through traditional forums of each region in Indonesia. As it grows by time, this is enforced in the court (Court Connected Mediation) as form of justice law